Promoting civic engagement through a service learning experience - Wee Yu Ghee; Farok Zakaria (Vol. 2 No. 12 [Special Issue - June 2012], 2012)
In recent decades, many indicators of civic involvement among adolescents have declined. While debate continues about advantages and disadvantages of mandating community service in universities, the practice of compelling adolescents to participate in community service is increasingly common. This study explores the civic behaviours, opinions, knowledge and dispositions of undergraduate students through their participation in a communitybased intercultural leadership program in Vietnam. In this program, students from six different countries were made to visit poor village entrepreneurs and offer their assistance in business improvement. Preliminary findings suggest that students who are competent for civic action, justice oriented, personally responsible and have high civic accountability, enjoy the service learning experience in the village. Students who rate the community service program as meaningful, exciting and educational are more compelled to participate voluntarily in the coming year. The goal of this research is to affirm a set of civic measures that are appropriate for use with youth participants in community service so as to promote civic education and inculcate civic engagement as lifelong practice.